INTELLECTUAL CAPITAL: influence on asset specificities (Gestão & Regionalidade, 2020)
The intellectual capital (IC) is gaining prominence both in academic studies as in the business context. When evaluated the development of these elements, the Brazilian agribusiness stands out. Some difficulties are being addressed by studies linked to the transaction cost economics (TCE), resembling mainly with asset specificities. This study aims to understand how the influence of the components of intellectual capital in the formation of asset specificity in the downstream transactions of agribusiness companies. The quantitative method demonstrated relevant to the objective with the companies listed in the Exame M&M 2016, in which a multiple linear regression was performed. Three components of IC are present in the context of agribusiness, but only the structural component has been shown to be significant for the formation of asset specificities. Through this result, managers can identify points of specificities, which can be work in order to carry out efficient transactions.
Keywords: Intellectual Capital; Asset Specificities; Agribusiness